2016
DOI: 10.1080/00909882.2016.1192289
|View full text |Cite
|
Sign up to set email alerts
|

Social media and corporate reputation during crises: the viability of video-sharing websites for providing counter-messages to traditional broadcast news

Abstract: Exemplification, or the use of highly emotional and arousing messages to elicit responses based on impression formation, has been shown to influence perceptions of events, individuals, and organizations. News coverage concerning the use of lean finely textured beef (LFTB) is one such example, and anecdotal evidence suggests that this coverage may have had a negative impact on public perception of the manufacturers producing LFTB. The current study examined the use of social media (specifically videosharing sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 43 publications
1
42
1
Order By: Relevance
“…When used strategically, exemplars can make complex information easier to understand and remember (Zillmann, 2006;Zillmann & Brosius, 2000). They can also be used to counter misleading negative exemplars, which often go viral on social media (D. D. Sellnow & Sellnow, 2014a;Spence et al, 2016). Incorporating positive exemplars may effectively reduce fear and heighten self-efficacy among disparate nonscientific publics receiving the messages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used strategically, exemplars can make complex information easier to understand and remember (Zillmann, 2006;Zillmann & Brosius, 2000). They can also be used to counter misleading negative exemplars, which often go viral on social media (D. D. Sellnow & Sellnow, 2014a;Spence et al, 2016). Incorporating positive exemplars may effectively reduce fear and heighten self-efficacy among disparate nonscientific publics receiving the messages.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to offer positive exemplars in the messages shared by the CDC, Dallas news stories, and international organization websites as a counter to them appears to be an unfortunate oversight. Research has reported that positive exemplars can be effective in countering negative ones, reducing fear, and fostering self-efficacy, but only if they are actually offered and received by target populations (D. D. Sellnow & Sellnow, 2014a;Spence et al, 2015;Spence, Sellnow-Richmond, Sellnow, & Lachlan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous exemplification research has looked at issues of susceptibility and severity of threats (Brosius & Bathelt, 1994;Spence et al, 2015Spence et al, , 2016Westerman et al, 2009, Westerman, Spence, andLachlan, 2012;Zillmann, Gibson, Sundar, & Perkins, 1996). Exemplification effects have been studied in numerous contexts and modalities.…”
Section: Online Comments and Organizational Reputationmentioning
confidence: 99%
“…Previous research has demonstrated that news stories containing exemplars can influence the perceptions of an organization's reputation (Spence et al, 2016). An organization's social legitimacy or responsibility is derived from how consumers and other stakeholders see the organization as managing risks in terms of the stakeholders' best interest (Palenchar, Hocke, & Heath, 2011).…”
Section: Online Comments and Organizational Reputationmentioning
confidence: 99%
“…Therefore corporations can pay attention to ethical and responsibility aspects in their social media posts. Given the positive relationship between issue-specific frames and negative sentiment, corporations may continually monitor social media posts and post emotional stories in an effort to elicit positive audience perceptions (Spence, Sellnow-Richmond, Sellnow, & Lachlan, 2016).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%